Implementasi Teori Riba Dalam Peraturan Perundang-Undangan Di Indonesia - Nugroho, Fahmi Hasan; Nurrohman, Nurrohman (ITB AAS INDONESIA Surakarta, 2024)
This research aims to elaborate on the extent of the application of the riba theory in the legislation in Indonesia. This research is a qualitative study using an analytical descriptive method towards data sources in the form of books and articles related to the discussed title. This research concludes that the riba theory in sharia is not fully implemented into the legislative system in Indonesia, this is because Indonesia chooses to adopt two economic systems to run together, moreover from the two forms of riba that are prohibited, only one form of riba that is the government’s concern, namely debt riba, while barter riba does not have a position except only in fatwa and financial institution products.